Variation in Flavonoid Composition and Radical-Scavenging Activity in Ginkgo biloba L. due to the Growth Location and Time of Harvest - Laura Rimkiene; Asta Kubiliene; Andrejus Zevzikovas; Daiva Kazlauskiene; Valdas Jakstas (Journal of Food Quality)
The aim of our research is to investigate the qualitative and quantitative composition and antioxidant activity of flavonoids in leaf samples of Ginkgo biloba L. (G. biloba) growing in Lithuania and also to provide practical recommendations for the pharmaceutical industry to determine the optimum harvesting time and growth location of G. biloba leaves. The obtained results indicate that the growth location and time of sample collection have a significant influence (p≤0.05) on the content of active compounds. July and August are the best months to harvest G. biloba leaves for industry. To ensure the rational collection of G. biloba raw material, the location of plantations is recommended in the western and southwestern phytoregions. The obtained results also indicate that the flavonoid content in G. biloba leaf has a significantly positive correlation (r=0.952, p≤0.001) with antioxidant activity. The aqueous acetonic extracts from green leaves scavenge radicals to a greater degree than those from yellow Ginkgo leaves. The results of this investigation provide information regarding the most suitable Lithuanian growing location to produce G. biloba with an optimized content of health-promoting compounds.